JUN and PDGFRA as Crucial Candidate Genes for Childhood Autism Spectrum Disorder - Li, Heli; Wang, Xinyuan; Hu, Cong; Li, Hao; Xu, Zhuoshuo; Lei, Ping; Luo, Xiaoping; Hao, Yan (Frontiers in Neuroinformatics, 2022)
Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder, characterized by marked genetic heterogeneity. In this study, two independent microarray datasets of cerebellum of ASD were integrative analyzed by NetworkAnalyst to screen candidate crucial genes. NetworkAnalyst identified two up-regulated genes, Jun proto-oncogene (JUN) and platelet derived growth factor receptor alpha (PDGFRA), as the most crucial genes in cerebellum of ASD patients. Based on KEGG pathway database, genes associated with JUN in the cerebellum highlight the pathways of Th17 cell differentiation and Th1 and Th2 cell differentiation. Genes associated with PDGFRA in the cerebellum were found enriched in pathways in EGFR tyrosine kinase inhibitor resistance and Rap1 signaling pathway. Analyzing all differentially expressed genes (DEGs) from the two datasets, Gene Set Enrichment Analysis (GSEA) brought out IL17 signaling pathway, which is related to the expression of JUN and PDGFRA. The ImmuCellAI found the elevated expression of JUN and PDGFRA correlating with increased Th17 and monocytes suggests JUN and PDGFRA may regulate Th17 cell activation and monocytes infiltrating. Mice model of maternal immune activation demonstrated that JUN and PDGFRA are up-regulated and related to the ASD-like behaviors that provide insights into the molecular mechanisms underlying the altered IL17 signaling pathway in ASD and may enable novel therapeutic strategies.